The search for instantaneous vection: An oscillating visual prime reduces vection onset latency - Palmisano, Stephen; Riecke, Bernhard E. (PLOS ONE, 2018)
Typically it takes up to 10 seconds or more to induce a visual illusion of self-motion (“vection”). However, for this vection to be most useful in virtual reality and vehicle simulation, it needs to be induced quickly, if not immediately. This study examined whether vection onset latency could be reduced towards zero using visual display manipulations alone. In the main experiments, visual self-motion simulations were presented to observers via either a large external display or a head-mounted display (HMD). Priming observers with visually simulated viewpoint oscillation for just ten seconds before the main self-motion display was found to markedly reduce vection onset latencies (and also increase ratings of vection strength) in both experiments. As in earlier studies, incorporating this simulated viewpoint oscillation into the self-motion displays themselves was also found to improve vection. Average onset latencies were reduced from 8-9s in the no oscillating control condition to as little as 4.6 s (for external displays) or 1.7 s (for HMDs) in the combined oscillation condition (when both the visual prime and the main self-motion display were oscillating). As these display manipulations did not appear to increase the likelihood or severity of motion sickness in the current study, they could possibly be used to enhance computer generated simulation experiences and training in the future, at no additional cost.
Keywords: Computerized simulations; DG2019; Motion; NSERC DG 2026; Priming (psychology); Riecke; Riecke_2018; Sensory perception; Vibration; Virtual reality; Vision; Visual impairments; bernhard-riecke; journalPaper; stephen-palmisano; vection